Copper Precipitation And Cyanide Recovery Pilot Testing For The Newmont Yanacocha Project - M. Botz; S. Acar (Society for Mining, Metallurgy & Exploration, 2007)
Introduction In 2007, Newmont Mining Corporation will begin construction of a milling and cyanidation leaching circuit for the Yanacocha site in Peru. Ore to be processed in the circuit contains a relatively high level of cyanide-soluble copper, and as a result, leach solutions are expected to contain elevated levels of copper and WAD cyanide. As the means of controlling copper levels in leach solution, a circuit will be installed to precipitate copper sulfide from barren solution using sodium hydrosulfide. In addition, a circuit will be installed to recover cyanide from barren solution, with recovered cyanide to be returned to the leaching circuit and treated solution to be utilized as make-up in existing heap leaching facilities. As needed to support design of the copper precipitation and cyanide recovery circuits, pilot testing was conducted in 2005 to determine preferred operating conditions and evaluate the performance of the processes. This paper presents results from the pilot testing where 99% copper reduction was achieved and 95% to 98% cyanide recovery was achieved.